Алгоритми сталого розвитку екологічної безпеки кислотного гідравлічного розриву пласта - Лижнюк, О. П.; Михайловська, О. В.; Бухкало, Світлана Іванівна; Агейчева, Олександра Олександрівна (Яроче́нко Я. В., 2025)
The essence of sustainable development of acid hydraulic fracturing is the application of two physicochemical effects on the bottomhole zone within the framework of one technological process. The impact on the composition of rocks occurs not only due to high pressures and rates of fracturing fluid injection, but also due to chemical reactions of acid with rocks. Acid treatment of rock is used in both carbonate rocks and sandstones. In sandstones, acid treatment of the matrix is aimed at dissolving particles that pollute the bottomhole zone of the formation and perforations. Theoretically, the acid is filtered into the porous medium, dissolving solid particles in the pore channels that impede the flow of formation fluid, so the acid dissolves particles in the pores, pore channels and along the pore surfaces
Keywords: екологічна безпека; карбонатні колектори; технології гідророзриву пласта; закачування робочих рідин; ієрархія складових процесів